The disappearing history - Pearl, Alexa, 1967- (Pearl, Alexa, 1967- Tales of Sasha, 2018)
"The History Day celebration is coming up in Crystal Cove, and Sasha has to pick her favorite story to read aloud. But when she unrolls the magical fabrics with the flying horse history on them, she discovers that all the words have disappeared! Can Sasha figure out what happened and find a way to return the stories to the fabrics in time for the celebration?"--